Allographic translation, self-translation and alloglottic rewriting : towards a digital edition of poetry by Pedro Homem de Mello - Pereira, Elsa (2021)
This chapter focuses on a series of interlingual materials related to the genetic dossier of 20th-century Portuguese author Pedro Homem de Mello (1904-1984), whose poetry is the object of an ongoing digital edition. Such documents may be organised into two main categories: a group of allographic translations (made by other persons than the poet) and a series of authorial witnesses, ranging from self-translation to alloglottic rewriting. The chapter starts by presenting examples of some of these occurrences and analyses their theoretical implications for an edition with a genetic orientation. It then proceeds to elaborate on the editorial approach adopted in the project and the use of the electronic medium to organise the digital archive.